Efektivitas Latihan Keseimbangan dan Latihan Penguatan untuk Mencegah Keseleo Pergelangan Kaki Berulang: Tinjauan Sistematis yang Komprehensif - Oktavia Indah Fitriningrum; Azmi Abdah; Febriana Febriana (Jurnal Sehat Mandiri, 2026)
Background: Ankle sprain is a sports injury with a high recurrence rate. Impaired proprioception, neuromuscular control, and postural stability are important factors that increase the risk of recurrent injury. Objective: To evaluate the effectiveness of balance training and strengthening exercises in preventing recurrent ankle sprains. Methods: This systematic review followed the PRISMA 2020 guidelines. Articles were retrieved from PubMed, ScienceDirect, and SagePub, with inclusion criteria consisting of English-language articles relevant to the topic and published between 2014 and 2024. Results: A total of 8 studies involving 267 participants met the inclusion criteria. The sample sizes of the included studies ranged from 18 to 54 participants. Most studies showed that balance training improved dynamic balance, proprioception, postural stability, and ankle function. Strengthening exercises also provided benefits in improving muscle strength; however, their effects on dynamic balance were more limited and less consistent. Conclusion: Balance training demonstrated more consistent effectiveness than strengthening exercises in preventing recurrent ankle sprains. Strengthening exercises may still be used as part of rehabilitation, particularly when combined with balance training.